Analysis of Gut Microbiota and Metabolites in Diannan Small Ear Sows at Diestrus and Metestrus - Guan, Xuancheng; Zhu, Junhong; Sun, Haichao; Zhao, Xiaoqi; Yang, Minghua; Huang, Ying; Pan, Hongbin; Zhao, Yanguang; Zhao, Sumei (Frontiers in Microbiology, 2022)
The physiological state of the host affects the gut microbes. The estrus cycle is critical to the reproductive cycle of sows. However, the association between gut microbes and animal estrus is poorly understood. Here, high-throughput 16S rRNA sequencing and LC-MS non-targeted metabolome technology were used to study the estrous cycles in Diannan small ear pigs. Significantly different gut microbiota and metabolites of sows at estrous and diestrous were screened out, and the correlation was analyzed. We found that the intestinal microbial composition and microbial metabolism of Diannan small ear sows were significantly different at diestrus and metestrus. The abundances of Spirochaetes, Spirochaetia, Spirochaetales, Spirochaetaceae, Deltaproteobacteria, unidentified_Alphaproteobacteria, Ruminococcus_sp_YE281 and Treponema_berlinense in intestinal microorganisms of Diannan small ear sows at metestrus are significantly higher than that at diestrus. Propionic acid, benzyl butyrate, sucrose, piperidine, and AICAR were significantly enriched at metestrus compared with at diestrus, which were involved the energy metabolism-related pathways and AMPK signaling pathway. At diestrus and metestrus, differential microbiota of unidentified_Alphaproteobacteria, Intestinimonas, Peptococcus, Terrisporobacter, and differential metabolites of piperidine, propionic acid and benzyl butyrate, sucrose, 4 - methyl catechol, and AICAR exists a certain degree of correlation. Therefore, unidentified_Alphaproteobacteria, Ruminococcus_sp_YE281, and Treponema_berlinense may have a potential role at metestrus of the Diannan small ear sows. AICAR may be a potential marker of estrus Diannan small ear sows feces. But further study the specific mechanism. These findings provide a new perspective for sows production management and improving of sows reproductive performance.